2004
DOI: 10.1089/neu.2004.21.1671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vimentin on Reactive Gliosis:In VitroandIn VivoAnalysis

Abstract: Reactive gliosis is a prominent result of many types of insult to the central nervous system (CNS) and leads to the formation of glial scar that impedes the regeneration of axons. The intermediate filament protein vimentin is found in pathology of the CNS, mainly in the vicinity of injuries to the CNS. In the present study we investigated the role of vimentin in the formation of glial scars in vitro and in vivo by using immunohistochemistry, Western blot analysis, and in situ hybridization. In vitro experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…jneurosci.org as supplemental material). This type of morphological change in astrocytes is similar to what occurs in reactive astrocytosis in vivo (Boukhelifa et al, 2003;Lin and Cai, 2004;Wilhelmsson et al, 2006). Hypertrophy of cellular processes and increased GFAP expression are two hallmarks of reactive astrocytes after all forms of neural injury in vivo (Wilhelmsson et al, 2004), suggesting the possibility that LCN2 may mediate reactive astrocytosis in vivo.…”
Section: Lcn2-induced Morphological Change Of Astrocytessupporting
confidence: 59%
“…jneurosci.org as supplemental material). This type of morphological change in astrocytes is similar to what occurs in reactive astrocytosis in vivo (Boukhelifa et al, 2003;Lin and Cai, 2004;Wilhelmsson et al, 2006). Hypertrophy of cellular processes and increased GFAP expression are two hallmarks of reactive astrocytes after all forms of neural injury in vivo (Wilhelmsson et al, 2004), suggesting the possibility that LCN2 may mediate reactive astrocytosis in vivo.…”
Section: Lcn2-induced Morphological Change Of Astrocytessupporting
confidence: 59%
“…Additionally, we are unsure as to the precise link between vimentin expression in individual reactive glia and the area of gliosis in songbirds. In mice, recent in vitro and in vivo studies report decreased astrocytic proliferation and glial scar formation, respectively, following compromise of vimentin expression by injection of RNA antisense to vimentin (Lin and Cai, 2004). These data suggest that vimentin is necessary for normal intermediate filament assembly and glial scar formation following central nervous system insult Pekny and Nilsson, 2005;Pekny et al, 1999).…”
Section: Discussionmentioning
confidence: 75%
“…Using primary astrocyte cultures of vimentin knock-out mice, it was pointed out that vimentin appeared to be necessary to stabilize GFAP filaments and the intermediate filament network formation [92]. Accordingly, in vitro transfection experiments showed that the growth of astrocytes is inhibited when vimentin expression is decreased [99]. …”
Section: Canine Distemper Leukoencephalitis — Novel Aspects Of Itsmentioning
confidence: 99%